Method for controlling influence of ore particle size matching on air permeability of material layer
By detecting the gas permeability of the furnace material structure matching in the blast furnace iron smelting under a reducing atmosphere of 500℃~1600℃, and optimizing the ore particle size matching relationship. The mixed charge of large and small ore is used to solve the problem of insufficient breathability of the cutting layer with high pellet ore ratio, and achieving efficient and low-cost iron smelting production.
Patent Information
- Application Number
- CN202411893792.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
During blast furnace ironmaking, it is difficult for the prior art to maintain the air permeability of the material layer while ensuring the reaction rate. Especially under high pellet ore ratio, there are challenges in controlling the influence of ore particle size matching on the air permeability of the material layer.
The air permeability of the furnace material structure of ore + coke with different ore particle size matching in a reducing atmosphere of 500℃~1600℃, and the matching relationship between ore of different particle sizes is optimized according to the detection results. The mixture of large-grain ore and small-grain ore is used for charging to improve the air permeability of the material layer.
With the high proportion of pellet ore entering the furnace, the air permeability of the furnace material structure is improved, thereby promoting high yield, low consumption, emission reduction and cost reduction of blast furnaces.
Smart Images

Figure CN119614775A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ironmaking, and more specifically, relates to a method for controlling the influence of ore particle size matching on the permeability of a material layer under a high pellet ratio. Background Art
[0002] Pelletized ore is a spherical artificial iron ore made by mixing fine concentrate powder and other additives, adding water and rolling it into balls on a pelletizing machine, and then drying and high-temperature roasting to consolidate it. Its main components include SiO2, Al2O3, CaO, MgO, TFe, Mn, P, S, etc., as well as a small amount of K2O, Na2O, FeO, Ni and other elements. In the blast furnace ironmaking process, revealing the critical particle size is of great significance for optimizing production efficiency. For the ironmaking process, in order to ensure the stability of the ironmaking process, it is necessary to control the particle size of the raw materials involved in the blast furnace, such as sintered ore and pelletized ore. Before entering the furnace, smaller ore particles will be screened out, which means that the particle size of the ore particles in the blast furnace is different. Therefore, it is necessary to understand the particle size effect in the ironmaking process. However, most of the work focuses on reduction kinetics or particle size segregation, ignoring the batch transformation caused by size effect. Taking the gaseous reduction of iron oxides during heating as an example, due to the large specific surface area, small-sized iron oxides have a faster reaction rate, while the smaller space in the material layer is bound to deteriorate its permeability, especially when the metallic iron gradually melts at a higher temperature and fills the internal pores. The study of the critical size effect of pellets in the direct reduction process found that the optimal size is 8~10mm, because larger pellets hinder mass transfer and heat transfer, and the permeability of the material layer is reduced when the particles are smaller than 8mm. For sintered ore, the change of sintering mixture brings obvious size effect. The results of the effect of limestone particle size on sintered ore show that when the limestone particle size is between 1.25~1.52mm, the DRI of the sintered ore is better due to phase change. The particle size effect also affects the properties of sintered ore, such as return ore or material layer permeability. It is well known that smaller particles show faster reaction rates but poorer permeability. In contrast, larger particles have a decreased kinetic rate while maintaining superior permeability.
[0003] Therefore, there is an ongoing debate about the minimum size of iron ore to be used in practical blast furnace production. Summary of the invention
[0004] In view of this, the present invention proposes a method for controlling the effect of ore particle size matching on the permeability of the material layer under high pellet ratio, aiming to achieve a faster reaction rate of small particle ore in the blast furnace while taking into account better permeability.
[0005] In order to solve at least one of the above technical problems, the present invention adopts the following technical solution: According to the present invention, a method for controlling the influence of ore particle size matching on the permeability of a material layer under a high pellet ratio is provided, comprising: step S100, detecting the permeability of a charge structure of ore + coke with different ore particle size matching under a reducing atmosphere of 500°C to 1600°C, in volume percentage, wherein the reducing atmosphere comprises 0~100% CO+0~100% H2+0~99% N2; step S200, optimizing the matching relationship of ores of different particle sizes according to the detection result.
[0006] According to an embodiment of the present invention, in step S100, the charge is subjected to a soft melting dripping test in a reducing atmosphere at 500° C. to 1600° C., and the quality of the air permeability is determined based on the maximum pressure difference obtained.
[0007] According to one embodiment of the present invention, the charge structure of ore+coke is an "upper coke+ore+lower coke" structure.
[0008] According to one embodiment of the present invention, the particle size of coke is 1 mm to 60 mm, and the particle size of ore is 1 mm to 30 mm.
[0009] According to one embodiment of the present invention, the ore is 100% pelletized ore, or, in terms of mass percentage, the ore contains 50% to 99% pelletized ore + 1% to 50% sintered ore.
[0010] According to one embodiment of the present invention, the middle ore layer of the "upper coke + ore + lower coke" structure is loaded with a mixture of large-particle ore and small-particle ore, wherein the particle size of the large-particle ore is ≥8mm, and the particle size of the small-particle ore is <5mm.
[0011] According to an embodiment of the present invention, the method of mixing the large-particle ore and the small-particle ore includes: mixing the large-particle ore and the small-particle ore evenly and then loading.
[0012] According to an embodiment of the present invention, the method of mixing the large-particle ore and the small-particle ore includes: a left-right distribution type furnace charge structure of the large-particle ore and the small-particle ore.
[0013] According to one embodiment of the present invention, the large-particle ore and the small-particle ore are mixed in a manner that the small-particle ore is at the bottom and the large-particle ore is at the top.
[0014] According to one embodiment of the present invention, the large-particle ore and the small-particle ore are mixed in a manner that: the large-particle ore is at the bottom and the small-particle ore is at the top.
[0015] By adopting the above technical scheme, compared with the prior art, the present invention proposes a control method for the influence of ore particle size matching on the permeability of the material layer based on the charge structure with a high proportion of pellet ore entering the furnace (≥50%) (100% pellet ore, or 50%~99% pellet ore + 1%~50% sintered ore), which solves the problem that the permeability of the blast furnace cannot be accurately and objectively evaluated under the existing average particle size raw material or fuel material layer structure, specifically, the permeability of the charge structure of ore + coke with ore particle size matching is detected under a high-temperature reducing atmosphere. Applying the method according to the present invention to the production practice of blast furnaces can effectively promote high production, low consumption and emission reduction of blast furnaces, and is conducive to the refined operation of charge, which can reduce the screening rate of smaller ore particles, reduce the return of ore in blast furnaces, and reduce the costs of fuel and labor in sintering and pelletizing processes, thereby reducing the cost per ton of iron. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0017] Figure 1 A flow chart showing a method for controlling the effect of ore particle size matching on the permeability of a material layer under a high pellet ratio according to an embodiment of the present invention is shown; Figure 2 A schematic diagram of a furnace charge structure according to an embodiment of the present invention is shown; Figure 3 The diagram shows pressure difference diagrams of six kinds of charge structures based on a molten drop experiment according to an embodiment of the present invention. DETAILED DESCRIPTION
[0018] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0019] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.
[0020] In addition, reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0021] like Figure 1 As shown, according to a method for controlling the influence of ore particle size matching on the permeability of a material layer under a high pellet ratio of the present invention, the method generally comprises the following steps: Step S100, detecting the air permeability of a charge structure of ore + coke with different ore particle sizes in a reducing atmosphere at 500° C. to 1600° C., wherein the reducing atmosphere contains 0 to 100% CO + 0 to 100% H2 + 0 to 99% N2 in volume percentage; Step S200, optimizing the matching relationship of ores of different particle sizes according to the detection results.
[0022] The present invention proposes a method for controlling the permeability of the material layer by matching the ore particle size based on a charge structure with a high proportion of pellets (≥50%) (100% pellets, or 50%~99% pellets + 1%~50% sintered ore). The charge structure of ore + coke in step S100 is preferably an "upper coke + ore + lower coke" structure. Among them, the middle ore layer is charged in a mixed manner of large-particle ore and small-particle ore. The permeability of the charge is greatly affected by the ore particle size, and the matching relationship of the ore particle size is comprehensively considered. In an embodiment of the present invention, the coke particle size is 1mm~60mm, and the ore particle size is 1mm~30mm.
[0023] In step S100, the charge can be subjected to a soft melting dripping test in a reducing atmosphere at 500°C to 1600°C, and the air permeability is judged based on the maximum pressure difference obtained. The soft melting dripping test simulates the temperature, atmosphere and charge structure in the blast furnace, places the iron-containing raw material in the experimental device, and heats it to a high temperature state. During the experiment, the raw material will gradually soften, melt, and eventually drip into the collector below the device. By observing and recording the soft melting and dripping process of the raw material, its soft melting dripping performance can be evaluated, including characteristic parameters such as soft melting start temperature, dripping start temperature, and maximum pressure difference. Among them, the maximum pressure difference is the maximum pressure difference between the upper and lower raw material layers during the experiment, which can reflect the air permeability of the raw material during the soft melting and dripping process. The present invention judges the air permeability of charge structures of different ore particle sizes based on the maximum pressure difference obtained in the soft melting dripping experiment, that is, the smaller the maximum pressure difference, the better the air permeability of the material layer.
[0024] During the soft melting dripping experiment, the finer the ore particle size, the larger its specific surface area, and the increased contact area with the reaction gas, thereby accelerating the reaction speed and facilitating the soft melting dripping process; too fine particle size may lead to decreased permeability, because fine particles are more likely to form a tight stacking structure, affecting gas circulation. The present invention aims to control how large and small particle ores are arranged to obtain optimal permeability. Therefore, the particle size distribution range of coke and ore is relatively large. In an embodiment of the present invention, the distribution range of coke particle size can be 1mm~60mm, preferably 10mm~12.5mm, and the ore particle size is preferably 1mm~30mm.
[0025] In the embodiment of the present invention, the middle ore layer of the "upper coke + ore + lower coke" structure is loaded by mixing large ore particles and small ore particles, wherein the particle size of the large ore particles is ≥8mm and the particle size of the small ore particles is <5mm. Figure 2 As shown, the mixing methods of large-particle ore and small-particle ore include: A) large-particle ore and small-particle ore are mixed and then charged; B) large-particle ore and small-particle ore are distributed on the left and right of the charge structure; C) small-particle ore is at the bottom and large-particle ore is at the top; D) large-particle ore is at the bottom and small-particle ore is at the top. Those skilled in the art can design more types of mixing methods of large-particle ore and small-particle ore according to actual working conditions.
[0026] The following is a specific embodiment of the method for controlling the effect of ore particle size matching on the permeability of the material layer under high pellet ratio according to the present invention and its specific process parameters.
[0027] Example 1 This embodiment is a method for controlling the effect of ore particle size matching on the permeability of the material layer based on a charge structure of 55% pelletized ore + 45% sintered ore.
[0028] Step S100, detecting the air permeability of a charge structure of ore+coke with different ore particle sizes in a reducing atmosphere at 1000°C.
[0029] The charge was subjected to a soft melting dripping experiment in a reducing atmosphere (50% CO + 30% H2 + 20% N2) from low temperature to high temperature. The following 6 charge structures were loaded into a crucible with an inner diameter of 75 mm, and the charge layer thickness was about 60 mm: (1) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm, and sintered ore + pellets with a particle size of 2mm, of which 225g of sintered ore and 275g of pellets; (2) 30g of upper coke with a particle size of 10mm-12.5mm, 30g of lower coke with a particle size of 10mm-12.5mm, and sintered ore + pellets with a particle size of 8mm, of which 225g of sintered ore and 275g of pellets; (3) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure A shown in the figure has large-particle ore and small-particle ore arranged, that is, large-particle ore and small-particle ore are mixed and then charged, wherein the large particles are 8mm sintered ore + pellets (sintered ore 225g, pellets 275g), and the small particles are 2mm sintered ore + pellets (sintered ore 225g, pellets 275g); (4) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure B shown is arranged with large-particle ore and small-particle ore, that is, a charge structure of large-particle ore and small-particle ore distributed left and right, wherein the large particles are 8mm sintered ore + pellets (sintered ore 225g, pellets 275g), and the small particles are 2mm sintered ore + pellets (sintered ore 225g, pellets 275g); (5) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure C shown is arranged with large-particle ore and small-particle ore, that is, the lower part is small-particle ore, and the upper part is large-particle ore, wherein the large particles are 8mm sintered ore + pellets (sintered ore 225g, pellets 275g), and the small particles are 2mm sintered ore + pellets (sintered ore 225g, pellets 275g); (6) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure D shown is arranged with large-particle ore and small-particle ore, that is, large-particle ore at the bottom and small-particle ore at the top, wherein the large particles are 8 mm sintered ore + pellets (sintered ore 225 g, pellets 275 g), and the small particles are 2 mm sintered ore + pellets (sintered ore 225 g, pellets 275 g).
[0030] Step S200, optimizing the matching relationship of ores of different particle sizes according to the detection results.
[0031] Specifically, the pressure difference under each material layer structure after the experiment is as follows: Figure 3As shown. The maximum pressure differences of the six charge structures are 8.1kPa, 5.4kPa, 6.2kPa, 8.1kPa, 6.7kPa, and 5.4kPa, respectively. It can be seen that the pressure difference of the small particle (2mm ore) charge layer is about 1.5 times that of the large particle (8mm sintered ore) charge layer. Compared with charge structure A, charge structure D significantly reduces the pressure difference and improves the air permeability. Moreover, the pressure difference under the four sintered ore charge structures A, B, C, and D is between the pressure difference of a single 2mm sintered ore and a single 8mm sintered ore. Therefore, in terms of the air permeability of the charge layer, the D charge structure is preferred when laying the charge under the charge structure of 55% pellet ore + 45% sintered ore.
[0032] Example 2 This embodiment is a method for controlling the effect of ore particle size matching on the permeability of the material layer based on a charge structure of 60% pelletized ore + 40% sintered ore.
[0033] Step S100, detecting the air permeability of a charge structure of ore+coke with different ore particle sizes matched under a reducing atmosphere (90% CO+5% H2+5% N2) at 800°C.
[0034] Specifically, the following four charge structures were loaded into a crucible with an inner diameter of 75 mm, and the thickness of the charge layer was about 60 mm: (1) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure A shown is arranged with large-particle ore and small-particle ore, that is, large-particle ore and small-particle ore are mixed and then charged, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (2) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure B shown is arranged with large-particle ore and small-particle ore, i.e., a charge structure of large-particle ore and small-particle ore distributed left and right, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (3) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2The ore structure C shown is arranged with large-particle ore and small-particle ore, that is, the lower part is small-particle ore, and the upper part is large-particle ore, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (4) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure D shown is arranged with large-particle ore and small-particle ore, that is, large-particle ore at the bottom and small-particle ore at the top, wherein the large particles are 8 mm sintered ore + pellets (sintered ore 200 g, pellets 300 g), and the small particles are 2 mm sintered ore + pellets (sintered ore 200 g, pellets 300 g).
[0035] Step S200, optimizing the matching relationship of ores of different particle sizes according to the detection results.
[0036] Specifically, the pressure difference under each material layer structure is obtained after the soft melting dripping experiment. The matching relationship of ores of different particle sizes is optimized based on the experimental results. The results show that in terms of the permeability of the material layer, the D ore structure is preferred when placing the material under the furnace structure of 60% pellet ore + 40% sintered ore.
[0037] Example 3 This embodiment is a method for controlling the effect of ore particle size matching on the permeability of the material layer based on a charge structure of 80% pelletized ore + 20% sintered ore.
[0038] Step S100, detecting the air permeability of a charge structure of ore+coke with different ore particle sizes matched under a reducing atmosphere (10% CO+80% H2+10% N2) at 1600°C.
[0039] Specifically, the following four charge structures were loaded into a crucible with an inner diameter of 75 mm, and the thickness of the charge layer was about 60 mm: (1) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure A shown is arranged with large-particle ore and small-particle ore, that is, large-particle ore and small-particle ore are mixed and then charged, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (2) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2The ore structure B shown is arranged with large-particle ore and small-particle ore, i.e., a charge structure of large-particle ore and small-particle ore distributed left and right, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (3) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure C shown is arranged with large-particle ore and small-particle ore, that is, the lower part is small-particle ore, and the upper part is large-particle ore, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (4) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure D shown is arranged with large-particle ore and small-particle ore, that is, large-particle ore at the bottom and small-particle ore at the top, wherein the large particles are 8 mm sintered ore + pellets (sintered ore 200 g, pellets 300 g), and the small particles are 2 mm sintered ore + pellets (sintered ore 200 g, pellets 300 g).
[0040] Step S200, optimizing the matching relationship of ores of different particle sizes according to the detection results.
[0041] Specifically, the pressure difference under each material layer structure is obtained after the soft melting dripping experiment. The matching relationship of ores of different particle sizes is optimized based on the experimental results. The results show that in terms of the permeability of the material layer, the D ore structure is preferred when placing the material under the furnace structure of 80% pellet ore + 20% sintered ore.
[0042] Example 4 This embodiment is a method for controlling the effect of ore particle size matching on the permeability of the material layer based on a charge structure of 95% pelletized ore + 5% sintered ore.
[0043] Step S100, detecting the air permeability of a charge structure of ore+coke with different ore particle sizes in a reducing atmosphere (90% CO +10% N2) at 500°C.
[0044] Specifically, the following four charge structures were loaded into a crucible with an inner diameter of 75 mm, and the thickness of the charge layer was about 60 mm: (1) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2The ore structure A shown is arranged with large-particle ore and small-particle ore, that is, large-particle ore and small-particle ore are mixed and then charged, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (2) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure B shown is arranged with large-particle ore and small-particle ore, i.e., a charge structure of large-particle ore and small-particle ore distributed left and right, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (3) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure C shown is arranged with large-particle ore and small-particle ore, that is, the lower part is small-particle ore, and the upper part is large-particle ore, wherein the large particles are 8mm sintered ore + pellets (sintered ore 200g, pellets 300g), and the small particles are 2mm sintered ore + pellets (sintered ore 200g, pellets 300g); (4) 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke with a particle size of 10mm~12.5mm and Figure 2 The ore structure D shown is arranged with large-particle ore and small-particle ore, that is, large-particle ore at the bottom and small-particle ore at the top, wherein the large particles are 8 mm sintered ore + pellets (sintered ore 200 g, pellets 300 g), and the small particles are 2 mm sintered ore + pellets (sintered ore 200 g, pellets 300 g).
[0045] Step S200, optimizing the matching relationship of ores of different particle sizes according to the detection results.
[0046] Specifically, the pressure difference under each material layer structure is obtained after the soft melting dripping experiment. The matching relationship of ores of different particle sizes is optimized based on the experimental results. The results show that in terms of the permeability of the material layer, the D ore structure is preferred when placing the material under the furnace structure of 95% pellet ore + 5% sintered ore.
[0047] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0048] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for controlling the effect of ore particle size matching on the permeability of a material layer, characterized in that: include: Step S100, detecting the air permeability of a charge structure of ore + coke with different ore particle sizes in a reducing atmosphere at 500° C. to 1600° C., wherein the reducing atmosphere contains 0 to 100% CO + 0 to 100% H2 + 0 to 99% N2 in volume percentage; Step S200, optimizing the matching relationship of ores of different particle sizes according to the detection results.
2. The method according to claim 1, characterized in that In the step S100, the charge is subjected to a soft melting dripping test in a reducing atmosphere at 500°C to 1600°C, and the quality of the air permeability is determined based on the maximum pressure difference obtained.
3. The method according to claim 2, characterized in that The charge structure of ore+coke is an "upper coke+ore+lower coke" structure.
4. The method according to claim 3, characterized in that The coke particle size is 1mm~60mm, and the ore particle size is 1mm~30mm.
5. The method according to claim 3, characterized in that: The ore is 100% pelletized ore, or, in terms of mass percentage, the ore contains 50% to 99% pelletized ore + 1% to 50% sintered ore.
6. The method according to claim 5, characterized in that The middle ore layer of the "upper coke + ore + lower coke" structure is loaded in a mixed manner of large-particle ore and small-particle ore, wherein the particle size of the large-particle ore is ≥8mm, and the particle size of the small-particle ore is <5mm.
7. The method according to claim 6, characterized in that The method of mixing the large-particle ore and the small-particle ore includes: mixing the large-particle ore and the small-particle ore evenly and then loading.
8. The method according to claim 6, characterized in that The method of mixing the large-particle ore and the small-particle ore includes: a left-right distribution type furnace charge structure of the large-particle ore and the small-particle ore.
9. The method according to claim 6, characterized in that The method of mixing the large-particle ore and the small-particle ore includes: the small-particle ore is at the bottom and the large-particle ore is at the top.
10. The method according to claim 6, characterized in that The method of mixing the large-particle ore and the small-particle ore includes: the large-particle ore is at the bottom and the small-particle ore is at the top.